Pengaruh Pemanfaatan Elektronik Government Terhadap Kedisiplinan Guru Di Sekolah Madrasah Aliyah Negeri Enrekang Kabupaten Enrekang - Rasmawati, Rasmawati; Ansyari, Muh Isa; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine whether there was an effect of the use of electronic government on teacher discipline in Enrekang State Madrasah Aliyah School, Enrekang Regency. This study used the method. Data collection techniques using a questionnaire in the form of a checklist and documentation. The data were analyzed using descriptive statistics with a simple linear regression formula. The data was explained in the form of tables, frequency and narrative of the processed data with the help of SPSS. The results showed that there was an effect of the use of electronic government on teacher discipline at the Enrekang Enrekang District Madrasah Aliyah which was very significant, namely the effect of efficiency (X1) on teacher discipline (Y) of 0.012 or 1.2%, Effect of effectiveness (X2) on discipline teacher (Y) was 0.073 or 7.3%, The effect of transparency (X3) on teacher discipline (Y) was 0.076 or 7.6%, the effect of accountability (X4) on teacher discipline (Y) was 0.161 or 16.1% which showed that the use of electronic government affects teacher discipline and the rest was influenced by other variables that had not been examined in this study. Therefore, the hypothesis in the study was accepted because it was supported by a significance value.Keywords: Influence, Utilization of Electronic Government, Teacher Discipline